2017
DOI: 10.1111/zph.12364
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E in southern Vietnam: Seroepidemiology in humans and molecular epidemiology in pigs

Abstract: | on behalf of the VIZIONS consortium †This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited. The detection of HEV RNA in pigs indicates that HEV may be a zoonotic disease risk in this location, although a larger sample size is required to infer an association between HEV positivity in pigs and seroprevalence in humans. K E Y W O R D Shepatitis E virus, human, pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
1
18
0
2
Order By: Relevance
“…Our samples are from individuals who have attended hospital for some reason, so are not fully representative of the population. However, for the younger individuals, we would assume this would bias the study towards finding positive individuals as in Berto et al [ 35 ], which we did not. For older individuals, this may be more representative of the population as a whole and as the exposure is assumed to be over 30 years ago, it is reasonable to assume this hospital visit is unrelated to the CHIKV infection exposure.…”
Section: Discussionmentioning
confidence: 86%
“…Our samples are from individuals who have attended hospital for some reason, so are not fully representative of the population. However, for the younger individuals, we would assume this would bias the study towards finding positive individuals as in Berto et al [ 35 ], which we did not. For older individuals, this may be more representative of the population as a whole and as the exposure is assumed to be over 30 years ago, it is reasonable to assume this hospital visit is unrelated to the CHIKV infection exposure.…”
Section: Discussionmentioning
confidence: 86%
“…We have previously shown that HEV circulates among healthy Vietnamese individuals and in hepatitis B virus-infected patients with anti-HEV immunoglobulin (Ig)G seroprevalences of 31% and 45%, respectively [23]. A previous study found 19.1% and 8.2% positivity of HEV-3 viral ribonucleic acid (RNA) in fecal samples and in rectal swabs from pigs, respectively, as well as a HEV seroprevalence of 16% in pig farmers in southern Vietnam [24]. However, the molecular epidemiology of HEV infection both in animals and humans is not yet completely understood.…”
mentioning
confidence: 99%
“…In Vietnam, the first HEV outbreak in humans was reported in 1994 along the river bordering Cambodia in the southwestern part [ 19 ]. One study showed that HEV is circulating in pigs (prevalence: 19.1% in fecal samples and 8.2% in rectal samples) while humans showed 31.7% seroprevalence [ 20 ]. In addition, a recent study in Vietnam found that pig farmers, slaughterhouse workers and pork meat retailers had high seroprevalence compared to unexposed groups [ 21 ].…”
Section: Introductionmentioning
confidence: 99%